Partial Amputation of a Nonreducing Prolapsed Phallus in an Ostrich (Struthio camelus) - Lima, Heloísa C. [UNESP]; Alves, Arthur C. T. [UNESP]; Mendes, Madalena R. C. [UNESP]; Moresco, Anneke; Rahal, Sheila C. [UNESP] (Association of Avian Veterinarians (AAV), 2023)
A 19-year-old male ostrich (Struthio camelus) was referred to a veterinary teaching hospital (São Paulo State University, Botucatu, Brazil) due to a 6-month history of recurrent prolapse of the phallus. On physical examination, 2 ulcerative wounds were present on the phallus, as well as caseous plaques and myiasis. Conservative treatment resulted in improvement but prolapse of the phallus remained. Thus, a decision was made to perform a partial phallectomy. The surgery was successful and no postoperative complications occurred. When the ostrich was reexamined 6 months postsurgery, the ostrich was alert, in good health, and the surgical site completely healed. The owner verbally reported no recurrence of the phallus prolapse 1 year after surgery.
Keywords: avian; ostrich; phallus; prolapse; ratite; reproductive disease; Struthio camelus; surgery